Alloy catalyst for fuel cell and preparation method thereof

By doping heteroatoms on the carbon support of the fuel cell catalyst and carrying out specific heat treatment solutions, the problem of particle agglomeration of the catalyst during high-temperature alloying treatment is solved, the activity and stability of the catalyst are improved, and it is suitable for large-scale industrial production.

CN119542439AActive Publication Date: 2025-02-28SHENZHEN ACAD OF AEROSPACE TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411776606.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing fuel cell catalysts are prone to particle agglomeration during high-temperature alloying treatment, resulting in reduced electrochemical activity and insufficient durability.

Method used

By doping heteroatoms on the carbon support and performing low-temperature heat treatment under a reducing gas atmosphere, the Pt-heteroatom-carbon support interaction is used to inhibit agglomeration during the alloying process.

Benefits of technology

It effectively improves the catalytic activity and stability of Pt-M/C alloy catalyst, extends its application life, and simplifies the preparation process, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542439A_ABST
    Figure CN119542439A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an alloy catalyst for a fuel cell, which comprises the following steps: mixing heteroatom-containing acid with carbon carrier powder, stirring, filtering, cleaning and drying to obtain a modified carbon carrier; mixing the modified carbon carrier with a solvent to form a carbon carrier solution mixture; adding a platinum source compound, an M metal source compound and a reducing agent for reaction, filtering, cleaning and drying to obtain a primary semi-finished product; placing the primary semi-finished product in an atmosphere furnace and a tubular furnace, introducing a reducing gas, heating to a temperature T1, reacting for a certain time, heating to a temperature T2, reacting for a certain time, and cooling to room temperature to obtain a secondary semi-finished product; putting the secondary semi-finished product into an acid solution with a certain concentration, reacting for a certain time at a certain temperature, filtering, cleaning and drying to obtain a tertiary semi-finished product; and heating and cooling the tertiary semi-finished product to obtain the alloy catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy fuel cells, and in particular relates to an alloy catalyst for fuel cells and a preparation method thereof. Background Art

[0002] At present, proton exchange membrane fuel cells mainly use Pt-based precious metal catalysts, the most typical of which is carbon-supported platinum (Pt / C) catalyst. However, Pt-based catalysts have high requirements for Pt metal loading, which leads to poor durability and low mass activity. In response to the above problems, Pt-M / C alloy catalysts (M = Ni, Co, Fe, Cu, Zn, Cr) have been developed in recent years. Compared with traditional catalysts, the electrical performance is greatly improved, especially as a cathode catalyst for fuel cells, the Pt-M / C alloy catalyst has great application prospects. In order to further improve the performance of the Pt-M / C alloy catalyst, the Pt-M / C alloy catalyst needs to be subjected to high-temperature alloying treatment in the latter part of the preparation process. The purpose is to make the different metal atoms in the catalyst rearrange regularly to form an ordered alloy structure, thereby improving the stability and durability of the catalyst, extending its application life, and reducing the dissolution of different metals in the Pt-M / C alloy catalyst during the long-term actual use of the fuel cell, which causes a decrease in performance.

[0003] However, the general high-temperature alloying treatment scheme is to place the catalyst semi-finished product in an inert gas atmosphere and calcine it at a certain high temperature, with the treatment temperature being greater than 500 degrees. The biggest problem with this process is that as the high-temperature treatment time increases, the catalyst nanoparticles agglomerate, causing the particle size to increase, reducing the electrochemical activity and the fuel cell performance.

[0004] In order to reduce the problem of agglomeration of catalyst particles during high-temperature alloying, researchers have tried various methods, including doping the catalyst carrier with heteroatoms (such as N, S, Mn, P, B), using the strong interaction between platinum-heteroatom-carbon carrier to anchor the catalyst Pt-M alloy particles and inhibit agglomeration during alloying. This method requires mixing the heteroatom-containing compound with the carrier and calcining it at high temperature so that the heteroatoms form bonds with the carbon atoms. However, high-temperature calcination can also have negative effects, such as the loss of active sites on the carrier and the decomposition of some functional groups on the surface of the carrier, which makes it impossible to evenly disperse the catalyst when using this type of carrier for liquid phase synthesis, and destroys the pore structure of the carrier. Ultimately, it is difficult to evenly disperse the catalyst particles on the carrier during the synthesis of the catalyst using this type of carrier, and the performance of the prepared catalyst sample deteriorates. Summary of the invention

[0005] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an alloy catalyst for a fuel cell and a preparation method thereof. The alloy catalyst for a fuel cell provided by the present invention has a novel and unique structure and has excellent catalyst activity and stability. At the same time, the preparation method has a simple process flow and is suitable for application in large-scale industrial production.

[0006] To this end, in the first aspect, an embodiment of the present invention provides a method for preparing an alloy catalyst for a fuel cell, the preparation method comprising: adding an acid containing a heteroatom into water to form an acid solution, adding a carbon carrier powder, mixing and stirring at a certain temperature for a certain time to dope the surface of the carbon carrier with an acid radical group containing a heteroatom, and then filtering, washing and drying to obtain a modified carbon carrier; mixing the modified carbon carrier with a solvent to form a carbon carrier solution mixture; adding a platinum source compound, an M metal source compound, a reducing agent and a carbon carrier solution mixture into a reactor in a certain proportion, reacting at a certain temperature for a certain time, and then The primary semi-finished product is obtained after filtering, washing and drying; the primary semi-finished product is placed in an atmosphere furnace, a tubular furnace and the like, a reducing gas is introduced, the temperature is raised to T1 for reaction for a certain time, the temperature is then raised to T2 for reaction for a certain time, and the secondary semi-finished product is obtained after cooling to room temperature; the secondary semi-finished product is placed in an acid solution of a certain concentration, the temperature is reacted for a certain time at a certain temperature, the tertiary semi-finished product is obtained after filtering, washing and drying; the tertiary semi-finished product is placed in an atmosphere furnace, a tubular furnace and the like, a reducing gas is introduced, the temperature is raised to T3, the temperature is reacted for a certain time, the alloy catalyst is obtained after cooling to room temperature and taking out.

[0007] Preferably, the acid containing heteroatoms is one or more of sulfuric acid, sulfurous acid, nitric acid, nitrous acid, boric acid, phosphoric acid, phosphorous acid, and permanganic acid; the concentration of the acid solution is 0.1-20 mol / L; the mixing method is one or more of ball milling, sand milling, high-speed dispersion, ultrasonic dispersion, etc.; the stirring temperature is 20-100° C.; the stirring time is 30-300 min; and the drying method is vacuum drying.

[0008] Preferably, the mass ratio of heteroatom elements to carbon elements in the modified carbon carrier material is 0.01-5%; the solvent is one or more of ethylene glycol, water, oleylamine, diphenyl ether, dibenzyl ether, o-dichlorobenzene, chloroform, and tetralin.

[0009] Preferably, the platinum source compound is one or more of chloroplatinic acid, platinum acetylacetonate, potassium chloroplatinate, and platinum chloride; the M metal source compound is one or more of cobalt acetate, cobalt hydroxide, cobalt chloride, cobalt nitrate, cobalt sulfate, basic cobalt carbonate, cobalt acetylacetonate III, cobalt acetylacetonate II, copper acetate, copper hydroxide, copper chloride, copper nitrate, copper sulfate, copper acetylacetonate, ferric acetate, ferric hydroxide, ferric chloride, ferric acetylacetonate, nickel acetylacetonate, nickel hydroxide, nickel chloride, zinc nitrate, zinc chloride, zinc acetylacetonate, and chromium chloride; the reducing agent is one or more of sodium hypophosphite, formaldehyde, sodium borohydride, tetradecanediol, dimethylaminoborane, and borane-tert-butylamine complex; the reaction temperature is 90-300°C, and the reaction time is 30-1200min.

[0010] Preferably, the molar ratio of the platinum element in the platinum source compound to the M element in the M metal source compound is (1:1)-(5:1); the mass ratio of the platinum element in the platinum source compound to the carbon carrier is (5:95)-(7:3).

[0011] Preferably, the reducing gas is hydrogen, acetylene, a mixture of hydrogen and inert gas of a certain concentration, etc., the T1 temperature is 100-450° C., and the T1 temperature reaction time is 30-1200 min.

[0012] Preferably, the T2 temperature is 450-1000° C., and the T2 temperature reaction time is 30-1200 min.

[0013] Preferably, the acid solution is one or more of perchloric acid, nitric acid, sulfuric acid, and acetic acid, the acid solution concentration is 0.01-0.5 mol / L, the reaction temperature is 40-100° C., the reaction time is 60-1200 min, the cleaning agent is water, and the drying method is vacuum drying.

[0014] Preferably, the reducing gas is hydrogen, acetylene and a certain concentration of hydrogen-inert gas mixture; the T3 temperature is 200-400°C, the reaction time is 30-1200min, and the mass fraction of heteroatom elements in the alloy catalyst is 0.005-2%.

[0015] In a second aspect, an embodiment of the present invention provides an alloy catalyst for a fuel cell prepared by the method described in the first aspect, wherein the alloy catalyst includes a complex formed by a platinum element and a transition metal element, and the complex is supported on a carbon material; the transition metal is one or more of nickel, cobalt, iron, copper, chromium and zinc.

[0016] The preparation method provided by the present invention directly treats the carbon carrier with an acid containing heteroatom groups during the preparation process, and the heteroatom is doped in a group manner. At the same time, during the acid treatment process, the number of active sites on the surface of the carbon carrier will not only not be lost, but the active sites will be increased, so that the carrier dispersion of the catalyst prepared later is easier and the loading is more uniform. In addition, in view of the problem of particle agglomeration caused by general alloying process treatment, the preparation method provided by the present invention is in the process of preparing the heteroatom-doped carrier, in a reducing gas atmosphere, first heat-treated at a temperature lower than the alloying temperature, so that the heteroatom groups on the carrier are decomposed to form a heteroatom-doped carrier, and then heated to a temperature higher than the alloying temperature, and high-temperature alloying treatment is performed, using the interaction of Pt-heteroatom-carbon carrier to suppress the agglomeration problem during the alloying process, thereby effectively improving the catalytic activity and stability of the Pt-M / C alloy catalyst. At the same time, the preparation method process is simple, suitable for application in large-scale industrial production, and the preparation method process is simple, suitable for application in large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A flow chart of a method for preparing an alloy catalyst for a fuel cell provided in an embodiment of the present invention;

[0018] Figure 2 TEM image of the alloy catalyst prepared in Example 1 of the present invention;

[0019] Figure 3 TEM image of the alloy catalyst prepared in Example 6 of the present invention;

[0020] Figure 4 TEM image of the alloy catalyst prepared in Comparative Example 1 of the present invention;

[0021] Figure 5 This is a TEM image of the alloy catalyst prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0022] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0023] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides examples of various specific processes and materials, but those of ordinary skill in the art can appreciate the reusability of other processes and / or the use of other materials.

[0024] The object of the present invention is to provide an alloy catalyst for a fuel cell and a preparation method thereof, wherein the alloy catalyst comprises a complex formed by a platinum element and a transition metal element, wherein the complex is loaded on a carbon material; the transition metal is one or more of nickel, cobalt, iron, copper, chromium and zinc metal. Specifically, the alloy catalyst is a Pt-M / C alloy catalyst, wherein M can be one or more of nickel, cobalt, iron, copper, chromium and zinc metal. The preparation method comprises: firstly modifying the carbon carrier with an acid containing heteroatoms (wherein the heteroatom-acid can be: S-sulfuric acid, sulfurous acid; N-nitric acid, nitrous acid; B-boric acid; P-phosphoric acid, phosphorous acid; Mn-permanganic acid), increasing the number of active sites on the surface of the carbon carrier that are combined with the catalyst particles, and at the same time leaving the heteroatoms in the carbon carrier in the form of groups without high temperature calcination. After filtering and cleaning the modified carbon carrier, a platinum source, an M metal source compound, a reducing agent and a solvent are added to carry out a synthesis reaction to obtain a catalyst semi-finished product with uniform particle combination distribution and containing heteroatoms at the same time. After the catalyst semi-finished product is dried, it is first heat-treated at a temperature lower than the alloying temperature in a reducing gas atmosphere, and then heated to a temperature higher than the alloying temperature for alloying treatment. Finally, the catalyst semi-finished product after the alloying treatment is subjected to acid treatment and high-temperature treatment to finally obtain a Pt-M / C alloy catalyst doped with heteroatoms.

[0025] The preparation method provided by the present invention directly treats the carbon carrier with an acid containing heteroatom groups during the preparation process, and the heteroatom is doped in a group manner. At the same time, during the acid treatment process, the number of active sites on the surface of the carbon carrier will not only not be lost, but the active sites will be increased, so that the carrier dispersion of the catalyst prepared later is easier and the loading is more uniform. In addition, in view of the problem of particle agglomeration caused by general alloying process treatment, the preparation method provided by the present invention is due to the heteroatom-doped carrier in the preparation process, in a reducing gas atmosphere, first heat-treated at a temperature lower than the alloying temperature, so that the heteroatom groups on the carrier are decomposed to form a heteroatom-doped carrier, and then heated to a temperature higher than the alloying temperature, and high-temperature alloying treatment is performed, using the interaction of Pt-heteroatom-carbon carrier to suppress the agglomeration problem during the alloying process, thereby effectively improving the catalytic activity and stability of the Pt-M / C alloy catalyst. At the same time, the preparation method process is simple and suitable for application in large-scale industrial production.

[0026] The present invention provides a method for preparing an alloy catalyst for a fuel cell. Figure 1 As shown, the preparation method comprises the following steps:

[0027] Step S1: adding an acid containing a heteroatom into water to form an acid solution, adding carbon carrier powder, mixing and stirring at a certain temperature for a certain time, so that the surface of the carbon carrier is doped with an acid group containing a heteroatom, and then filtering, washing and drying to obtain a modified carbon carrier;

[0028] Among them, the acid containing heteroatoms can be one or more of sulfuric acid, sulfurous acid, nitric acid, nitrous acid, boric acid, phosphoric acid, phosphorous acid, and permanganic acid; the concentration of the acid solution is 0.1-20 mol / L, the mixing method adopts one or more of ball milling, sand milling, high-speed dispersion, ultrasonic dispersion, etc., the stirring temperature is 20-100°C, and the stirring time is 30-300min; the drying method is vacuum drying.

[0029] Step S2: mixing the modified carbon support with a solvent to form a carbon support solution mixture;

[0030] Wherein, the solvent and the mixing method are one or more of ball milling, sand milling, high-speed dispersion, ultrasonic dispersion, etc.

[0031] Step S3: adding a mixture of a platinum source compound, an M metal source compound, a reducing agent, and a carbon carrier solution into a reactor in a certain proportion, reacting at a certain temperature for a certain time, filtering, washing, and drying to obtain a primary semi-finished product;

[0032] Among them, the platinum source compound can be one or more of chloroplatinic acid, platinum acetylacetonate, potassium chloroplatinate, and platinum chloride; the M metal source compound can be one or more of cobalt acetate, cobalt hydroxide, cobalt chloride, cobalt nitrate, cobalt sulfate, basic cobalt carbonate, cobalt acetylacetonate III, cobalt acetylacetonate II, copper acetate, copper hydroxide, copper chloride, copper nitrate, copper sulfate, copper acetylacetonate, ferric acetate, ferric hydroxide, ferric chloride, ferric acetylacetonate, nickel acetylacetonate, nickel hydroxide, nickel chloride, zinc nitrate, zinc chloride, zinc acetylacetonate, and chromium chloride; the reducing agent is one or more of sodium hypophosphite, formaldehyde, sodium borohydride, tetradecanediol, dimethylaminoborane, and borane-tert-butylamine complex; the reaction temperature is 90-300°C, and the reaction time is 30-1200min.

[0033] In addition, in this step, after filtering the above-mentioned reactants, they can be washed with a liquid compatible with the solvent, such as water, ethanol, n-propanol, isopropanol, n-hexane, chloroform, to remove excess solvents, platinum source compounds, M metal source compounds, reducing agents and other impurities; the drying method can be vacuum drying.

[0034] Step S4: placing the primary semi-finished product in an atmosphere furnace, a tubular furnace or the like, introducing a reducing gas, heating the product to a temperature T1 for a certain period of time, then heating the product to a temperature T2 for a certain period of time, and cooling the product to room temperature to obtain a secondary semi-finished product;

[0035] Among them, the reducing gas can be hydrogen, acetylene gas and a certain concentration of hydrogen-inert gas mixture; the T1 temperature can be 100-450°C, and the T1 temperature reaction time can be 30-1200min; the T2 temperature can be 500-1000°C, and the T2 temperature reaction time can be 30-1200min.

[0036] In the embodiment of the present invention, at temperature T1, the platinum source, heteroatoms in the form of groups and carbon carriers in the primary semi-finished product form a Pt-heteroatom-carbon carrier interaction; at temperature T2, Pt-M in the primary semi-finished product is regularly rearranged to form an ordered alloy structure. It can be understood that the T1 temperature is higher than the decomposition temperature of the corresponding heteroatom group and lower than the alloying treatment temperature; the T2 temperature is higher than the alloying treatment temperature.

[0037] Step S5: placing the secondary semi-finished product into an acid solution of a certain concentration, reacting at a certain temperature for a certain time, filtering, washing and drying to obtain a tertiary semi-finished product;

[0038] Wherein, the acid solution is one or more of perchloric acid, nitric acid, sulfuric acid, and acetic acid, the acid solution concentration is 0.01-0.5 mol / L, the reaction temperature is 40-100° C., the reaction time is 60-1200 min, the cleaning agent is water, and the drying method is vacuum drying.

[0039] In this step, the secondary semi-finished product is placed in the acid solution to wash away surface impurities and M metal, so that there is more Pt metal on the surface, thereby further improving the catalyst performance, and washed with water to remove excess acid.

[0040] Step S6: placing the three semi-finished products in an atmosphere furnace, a tubular furnace or the like, introducing a reducing gas, heating to T3 temperature, reacting for a certain period of time, cooling to room temperature and taking out to obtain the alloy catalyst.

[0041] The reducing gas may be hydrogen, acetylene, or a mixture of hydrogen and inert gas of a certain concentration; the T3 temperature may be 200-400°C, the reaction time may be 30-1200 min, and the mass fraction of heteroatomic elements in the alloy catalyst may be 0.005-2%.

[0042] In this step, temperature T3 is lower than temperature T2. This is because the Pt-M ratio of the surface layer of the three semi-finished products changes after acid treatment in step S5. In order to make the arrangement of metal atoms on the surface of the catalyst after acid treatment more regular and stable, heat treatment is carried out. At the same time, in order not to cause particle agglomeration, temperature T3 is lower than temperature T2.

[0043] The preparation method provided by the present invention directly treats the carbon carrier with an acid containing heteroatom groups during the preparation process, and the heteroatom is doped in a group manner. At the same time, during the acid treatment process, the number of active sites on the surface of the carbon carrier will not only not be lost, but the active sites will be increased, so that the carrier dispersion of the catalyst prepared later is easier and the loading is more uniform. In addition, in view of the problem of particle agglomeration caused by general alloying process treatment, the preparation method provided by the present invention is due to the heteroatom-doped carrier in the preparation process, in a reducing gas atmosphere, first heat-treated at a temperature lower than the alloying temperature, so that the heteroatom groups on the carrier are decomposed to form a heteroatom-doped carrier, and then heated to a temperature higher than the alloying temperature, and high-temperature alloying treatment is performed, and the Pt-heteroatom-carbon carrier interaction is used to suppress the agglomeration problem during the alloying process, thereby effectively improving the catalytic activity and stability of the Pt-M / C alloy catalyst. At the same time, the preparation method process is simple and suitable for application in large-scale industrial production.

[0044] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0045] Modified carrier preparation:

[0046] Modified carrier 1:

[0047] 20 g of carbon powder XC-72 (Cabot Corporation, USA) was added with 3 L of 10 mol / L sulfuric acid solution prepared in advance, and placed in a jacketed glass reactor. The carbon carrier acid solution was heated to 70°C by oil bath circulation heating; then dispersed at a high speed of 10,000 rpm using a high-speed disperser for 250 min; filtered, and repeatedly washed with deionized water until the pH value of the liquid was 7; the dispersion was filtered, and vacuum dried at 100 degrees for 24 hours to obtain a modified carbon carrier 1.

[0048] Modified carrier 2:

[0049] Add 20 g of carbon black EC300J (Lion Corporation, Japan) to 1.8 L of a pre-prepared 20 mol / L phosphoric acid solution, and disperse it at 3000 rpm for 30 min using a high-speed disperser; filter, and wash repeatedly with deionized water until the pH value of the liquid reaches 7; filter the dispersion, and vacuum dry it at 100°C for 24 hours to obtain a modified carbon support 2.

[0050] Modified carrier 3:

[0051] Add 24 g of acetylene black (Nippon Electric Chemical Industry Co., Ltd.) into 4 L of a pre-prepared 10 mol / L nitric acid solution, and disperse it at 600 rpm using a 5 mm ball mill for 120 min; filter and wash repeatedly with deionized water until the pH value of the liquid reaches 7; filter the dispersion and vacuum dry it at 100 °C for 24 hours to obtain a modified carbon support 3.

[0052] Modified carrier 4:

[0053] 30 g of carbon nanotubes MWNT-10 (Shenzhen Nanoport Co., Ltd.) were added to 25 L of a pre-prepared permanganate solution with a concentration of 0.1 mol / L, and the mixture was dispersed in a nano sand mill at a speed of 3900 rpm for 70 min; the mixture was filtered and repeatedly washed with deionized water until the pH value of the liquid reached 7; the dispersion was filtered and vacuum dried at 100°C for 24 hours to obtain a modified carbon support 4.

[0054] Modified carrier 5:

[0055] 30 g of graphitized carbon powder SD600 (Shenzhen B&T New Energy Materials Co., Ltd.) was added to 18 L of a pre-prepared 2 mol / L permanganate solution, and ultrasonically dispersed at 60 Hz for 300 min at 20°C using an ultrasonic grinder; filtered, and repeatedly washed with deionized water until the pH value of the liquid reached 7; the dispersion was filtered, and vacuum dried at 100°C for 24 hours to obtain a modified carbon support 5.

[0056] Modified carrier 6:

[0057] 20 g of carbon powder XC-72 (Cabot Corporation, USA) was added with 10 L of 20 mol / L sulfuric acid solution prepared in advance, placed in a jacketed glass reactor, and the carbon carrier acid solution was heated to 100°C by oil bath circulation heating; then dispersed at a high speed of 15,000 rpm using a high-speed disperser for 300 min; filtered, and repeatedly washed with deionized water until the pH value of the liquid reached 7; filtered the dispersion, and vacuum dried at 100°C for 24 hours to obtain a modified carbon carrier 6.

[0058] Example 1

[0059] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0060] (1) 16 g of the modified carbon support 1 was added to 2 L of ethylene glycol and dispersed using a 5 mm ball mill at 400 rpm for 2 hours;

[0061] (2) taking out the dispersion, placing it in a 5L reactor, adding 14.9g of platinum acetylacetonate, 3.6g of basic cobalt carbonate and 1.2g of sodium hypophosphite, heating to 175°C for reaction for 200min; cooling to room temperature, taking out the reaction liquid, and repeatedly washing it with a large amount of water until the pH value reaches 7; filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0062] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 340° C. for 120 min in a 5% concentration hydrogen and nitrogen mixed gas atmosphere, then heating it to 700° C. for 60 min, and cooling it naturally to obtain a secondary semi-finished product;

[0063] (4) placing the secondary semi-finished product obtained in the previous step into a pre-prepared 0.1 mol / L perchloric acid aqueous solution, ultrasonicating for 30 minutes, heating to 80° C., treating for 600 minutes, filtering, repeatedly washing with water until the pH value is 7, filtering and drying to obtain a tertiary semi-finished product;

[0064] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, heated to 300° C. and treated for 60 minutes in a 5% concentration of hydrogen and nitrogen mixed gas atmosphere to obtain an alloy catalyst.

[0065] Figure 2 Shown is a TEM image of the alloy catalyst prepared in this example.

[0066] Example 2

[0067] The preparation process of the alloy catalyst for the fuel cell in this embodiment refers to that in Embodiment 1, the only difference is that the modified carbon carrier 1 in Embodiment 1 is replaced by the modified carbon carrier 2, and the other steps are the same as those in Embodiment 1.

[0068] Example 3

[0069] The preparation process of the alloy catalyst for the fuel cell in this embodiment refers to that in Embodiment 1, the only difference is that the modified carbon carrier 1 in Embodiment 1 is replaced by the modified carbon carrier 3, and the other steps are the same as those in Embodiment 1.

[0070] Example 4

[0071] The preparation process of the alloy catalyst for the fuel cell in this embodiment is similar to that in Embodiment 1, except that the modified carbon carrier 1 in Embodiment 1 is replaced by the modified carbon carrier 4, and the other steps are the same as those in Embodiment 1.

[0072] Example 5

[0073] The preparation process of the alloy catalyst for the fuel cell in this embodiment is similar to that in Embodiment 1, except that the modified carbon carrier 1 in Embodiment 1 is replaced by the modified carbon carrier 5, and the other steps are the same as those in Embodiment 1.

[0074] Example 6

[0075] The preparation process of the alloy catalyst for the fuel cell in this embodiment is similar to that in Embodiment 1, except that the modified carbon carrier 1 in Embodiment 1 is replaced by the modified carbon carrier 6, and the other steps are the same as those in Embodiment 1.

[0076] Figure 3 Shown is a TEM image of the alloy catalyst prepared in this example.

[0077] Example 7

[0078] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0079] (1) 16 g of the modified carbon support 1 was added to 2 L of diphenyl ether and dispersed using a sand mill at 2400 rpm for 4 hours;

[0080] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of platinum acetylacetonate, 2.7g of nickel acetylacetonate and 1.2g of tert-butylamine borane complex, heating to 220°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, and repeatedly washing the solution with a large amount of ethanol until the solution conductivity is less than 20us / cm, then repeatedly washing with a large amount of water until the pH value is 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0081] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 450° C. at a rate of 4° C. per minute in an acetylene gas atmosphere for 1200 min, then heating it to 700° C. for 90 min, and cooling it naturally to obtain a secondary semi-finished product;

[0082] (4) placing the secondary semi-finished product obtained in the previous step into a 0.5 mol / L nitric acid aqueous solution prepared in advance, ultrasonicating for 30 minutes, heating to 70° C., treating for 720 minutes, filtering, repeatedly washing with water until the pH value is equal to 7, filtering and drying to obtain a tertiary semi-finished product;

[0083] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300 degrees at a rate of 4 degrees per minute in an acetylene gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0084] Example 8

[0085] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0086] (1) 16 g of the modified carbon support 1 was added to 2 L of diphenyl ether and dispersed using a sand mill at 2400 rpm for 4 hours;

[0087] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of chloroplatinic acid, 2.1g of copper chloride and 1.2g of borane tert-butylamine complex, heating to 300°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, repeatedly washing with a large amount of n-hexane: ethanol mixture with a volume ratio of 1:1 until the solution conductivity is less than 20us / cm, then repeatedly washing with a large amount of water until the pH value is 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0088] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 100° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 30 minutes, then heating it to 1000° C. for 90 minutes, and cooling it naturally to obtain a secondary semi-finished product;

[0089] (4) placing the secondary semi-finished product obtained in the previous step into a pre-prepared 0.5 mol / L nitric acid aqueous solution, ultrasonicating for 30 minutes, heating to 70° C., treating for 720 minutes, filtering, repeatedly washing with water until the pH value is 7, filtering and drying to obtain a tertiary semi-finished product;

[0090] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0091] Example 9

[0092] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0093] (1) 16 g of the modified carbon support 1 was added to 2 L of pure water and dispersed using a sand mill at 2400 rpm for 4 hours;

[0094] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of potassium chloroplatinate, 2.1g of ferric nitrate and 8g of formaldehyde aqueous solution, heating to 90°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, and then repeatedly washing with a large amount of water until the pH value is 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0095] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 100° C. at a rate of 4° C. per minute in an acetylene gas atmosphere for 30 min, then heating it to 1000° C. for 90 min, and cooling it naturally to obtain a secondary semi-finished product;

[0096] (4) placing the secondary semi-finished product obtained in the previous step into a pre-prepared 0.5 mol / L perchloric acid aqueous solution, ultrasonicating for 30 minutes, heating to 80° C., treating for 1200 minutes, filtering, repeatedly washing with water until the pH value is 7, filtering and drying to obtain a tertiary semi-finished product;

[0097] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0098] Example 10

[0099] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0100] (1) 16 g of the modified carbon support 1 was added to 2 L of oleylamine and dispersed using a sand mill at 2400 rpm for 4 hours;

[0101] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of potassium chloroplatinate, 1.8g of chromium chloride and 8g of formaldehyde aqueous solution, heating to 290°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, washing it repeatedly with a large amount of ethanol until the solution conductivity is less than 20us / cm, then washing it repeatedly with a large amount of water until the pH value is 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0102] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating the product at a rate of 4 degrees per minute to 450° C. for 1200 min in an acetylene gas atmosphere, then heating the product to 1000° C. for 1200 min, and cooling the product naturally to obtain a secondary semi-finished product;

[0103] (4) placing the secondary semi-finished product obtained in the previous step into a pre-prepared 0.5 mol / L nitric acid aqueous solution, ultrasonicating for 30 minutes, heating to 70° C., treating for 720 minutes, filtering, repeatedly washing with water until the pH value is 7, filtering and drying to obtain a tertiary semi-finished product;

[0104] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0105] Embodiment 11

[0106] This embodiment provides an alloy catalyst for a fuel cell and a preparation method thereof, comprising the following steps:

[0107] (1) 16 g of the modified carbon support 1 was added to 2 L of ethylene glycol and dispersed using a sand mill at 2400 rpm for 4 hours;

[0108] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of potassium chloroplatinate, 1.8g of zinc acetylacetonate and 2.4g of sodium hypophosphite, heating to 190°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, and then repeatedly washing with a large amount of water until the pH value reaches 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0109] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 400° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 100 min, then heating it to 500° C. for 180 min, and cooling it naturally to obtain a secondary semi-finished product;

[0110] (4) The secondary semi-finished product obtained in the previous step is placed in a pre-prepared 0.5 mol / L sulfuric acid aqueous solution, ultrasonicated for 30 minutes, heated to 70°C, treated for 720 minutes, filtered, repeatedly washed with water until the pH value is 7, filtered and dried to obtain a tertiary semi-finished product.

[0111] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300° C. at a rate of 4 degrees per minute in a 5% hydrogen and nitrogen mixed gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0112] Example 12

[0113] (1) 16 g of the modified carbon support 1 was added to 2 L of ethylene glycol and dispersed using a sand mill at 2400 rpm for 4 hours;

[0114] (2) taking out the dispersion, putting it into a 5L reactor, adding 8g of potassium chloroplatinate, 1.75g ​​of nickel acetylacetonate, 0.9g of zinc acetylacetonate and 2.4g of sodium hypophosphite, heating to 190°C for reaction for 1200min, cooling to room temperature, taking out the reaction liquid, and then repeatedly washing with a large amount of water until the pH value is 7, filtering, and vacuum drying at 100°C for 24 hours to obtain a semi-finished product;

[0115] (3) placing the primary semi-finished product obtained in the previous step into a high-temperature atmosphere furnace, heating it to 400° C. at a rate of 4 degrees per minute in an acetylene gas atmosphere for 100 min, then heating it to 500° C. for 180 min, and cooling it naturally to obtain a secondary semi-finished product;

[0116] (4) placing the secondary semi-finished product obtained in the previous step into a pre-prepared 0.5 mol / L sulfuric acid aqueous solution, ultrasonicating for 30 minutes, heating to 70° C., treating for 720 minutes, filtering, repeatedly washing with water until the pH value is 7, filtering and drying to obtain a tertiary semi-finished product;

[0117] (5) The three semi-finished products obtained in the previous step are placed in a high-temperature atmosphere furnace, and heated to 300° C. at a rate of 4 degrees per minute in a 5% hydrogen and nitrogen mixed gas atmosphere for 60 minutes to obtain an alloy catalyst.

[0118] Comparative Example 1

[0119] The preparation process of the alloy catalyst for the fuel cell in this embodiment refers to that in Embodiment 1, the only difference is that the modified carbon carrier 1 in Embodiment 1 is replaced by carbon powder XC-72, and the other steps are the same as in Embodiment 1.

[0120] Figure 4 Shown is a TEM image of the alloy catalyst prepared in this example.

[0121] Comparative Example 2

[0122] The preparation process of the alloy catalyst for fuel cells in this embodiment refers to that in Embodiment 1, the only difference is that the modified carbon carrier 1 in Embodiment 1 is replaced by carbon black EC300, and the other steps are the same as in Embodiment 1.

[0123] Figure 5 Shown is a TEM image of the alloy catalyst prepared in this example.

[0124] Comparative Example 3

[0125] TEC36F52, a Pt-Co / C catalyst product from Tanaka Precious Metals Co., Ltd. of Japan.

[0126] Note: Comparative Examples 1 and 2 use unmodified carbon supports. Although unmodified carbon supports do not contain heteroatoms and heat treatment at temperature T1 is ineffective, in order to verify the effect of the technical solution of the present invention, the heat treatment method still uses the same processing flow as in the embodiment.

[0127] The products prepared in the above Examples 1-12 and Comparative Examples 1-3 were subjected to performance tests, including the following tests:

[0128] Electrochemically active area, output voltage in polarization curve, ratio of electrochemically active area to initial electrochemically active area after 30,000 cycles, and 1A / cm in polarization curve after 30,000 cycles 2 Output voltage and initial 1A / cm 2 The specific test method of the output voltage ratio refers to GBT20042.5-2009 "Proton Exchange Membrane Fuel Cell Part 5: Membrane Electrode Test Method" and T / CAAMTB 12-2020 "Proton Exchange Membrane Fuel Cell Membrane Electrode Test Method". The element content test uses a scanning electron microscope energy spectrometer (SEM-EDS) to test the content of heteroatom elements, carbon elements, oxygen elements, platinum elements and M elements in the modified carbon carrier material, and the molar ratio of different elements can be simply calculated by measuring the corresponding element content and the corresponding element molecular weight by SEM-EDS. Scanning electron microscope energy spectrometer (SEM-EDS) is a more common test method for quantitatively testing element content. Catalyst particle morphology and particle size Catalyst particle photos were taken by transmission electron microscopy TEM, and the average particle size and D90 particle size of Pt-M particles in the catalyst (the particle size corresponding to the cumulative particle size distribution number reaching 90%) were obtained by using particle size statistics software for particle photos. The specific test results are shown in Table 1.

[0129] Table 1. Test items and test results of Examples 1-12 and Comparative Examples 1-3

[0130]

[0131] The alloy catalysts prepared in Example 1, Example 6 and Comparative Example 1 and Comparative Example 2 were tested by transmission electron microscope (TEM). The results are as follows: Figure 2 , 3 , 4, and 5. By comparison, it is found that the alloy catalyst prepared by the preparation method provided by the present invention can effectively inhibit the agglomeration of nanoparticles during the alloying process, maintain the uniformity of the particle size, and effectively improve the activity of the alloy catalyst.

[0132] In addition, according to Table 1, it can be seen that the alloy catalyst particles obtained in Example 1 and Example 6 of the present invention are uniform in size and distribution, and no particle agglomeration phenomenon is found. Among them, Example 6 of the present invention has a higher acid concentration, a higher temperature, a larger dispersion linear velocity, and a longer dispersion time in the modified carbon carrier preparation process, so that the heteroatom element mass ratio in the carrier is higher. In the alloy catalyst prepared later, the heteroatom element mass is higher, and a stronger Pt-heteroatom-carbon carrier interaction can be formed, which can more effectively inhibit the particle agglomeration during the alloying process, so that the alloy catalyst particles are distributed more evenly on the carbon carrier, and are more difficult to agglomerate after alloying treatment, and finally the particle size of the prepared alloy catalyst is smaller, more uniform, and the electrochemical active area is higher, and the output voltage is higher at the same current density. After 30,000 cycles, the electrochemical active area and the output voltage retention rate at the same current density are higher. However, the alloy catalyst particles obtained in Comparative Examples 1 and 2 are unevenly distributed, and obvious agglomeration occurs during the alloying process, and the final catalyst performance is poor.

[0133] In addition, according to Table 1, it can be seen that the alloy catalysts for fuel cells prepared in Examples 1-12 of the present invention have a higher electrochemical active area and a higher output voltage at the same current density than the alloy catalysts prepared in Comparative Example 1 and Comparative Example 2, which indicates that the alloy catalyst prepared by the preparation method provided by the present invention has a greater output power.

[0134] In addition, it can be seen from Table 1 that the alloy catalysts for fuel cells prepared in Examples 1-12 of the present invention have higher electrochemical active areas and output voltage retention rates at the same current density after 30,000 cycles than the alloy catalysts prepared in Comparative Examples 1 and 2 and the catalyst in Comparative Example 3. This indicates that the alloy catalysts prepared by the preparation method provided by the present invention have better durability.

[0135] At the same time, it can be seen from Example 12 of the present invention that the preparation method provided by the present invention can still achieve good results when preparing a ternary alloy Pt-Ni-Zn / C catalyst in which the M metals are Ni and Zn, indicating that the preparation method provided by the present invention is also suitable for the preparation of a multi-component Pt-M / C catalyst.

[0136] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0137] Although embodiments of the present invention have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing an alloy catalyst for a fuel cell, characterized in that: The preparation method comprises: Step S1: adding an acid containing a heteroatom into water to form an acid solution, adding carbon carrier powder, mixing and stirring at a certain temperature for a certain time, so that the surface of the carbon carrier is doped with an acid group containing a heteroatom, and then filtering, washing and drying to obtain a modified carbon carrier; Step S2: mixing the modified carbon support with a solvent to form a carbon support solution mixture; Step S3: adding a mixture of a platinum source compound, an M metal source compound, a reducing agent and a carbon carrier solution into a reactor in a certain proportion, reacting at a certain temperature for a certain time, filtering, washing and drying to obtain a primary semi-finished product; Step S4: placing the primary semi-finished product in an atmosphere furnace, a tubular furnace or the like, introducing a reducing gas, heating the product to a temperature T1 for a certain period of time, then heating the product to a temperature T2 for a certain period of time, and cooling the product to room temperature to obtain a secondary semi-finished product; Step S5: placing the secondary semi-finished product into an acid solution of a certain concentration, reacting at a certain temperature for a certain time, filtering, washing and drying to obtain a tertiary semi-finished product; Step S6: placing the three semi-finished products in an atmosphere furnace, a tubular furnace or the like, introducing a reducing gas, heating to T3 temperature, reacting for a certain period of time, cooling to room temperature and taking out to obtain the alloy catalyst.

2. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In step S1, the acid containing heteroatoms is one or more of sulfuric acid, sulfurous acid, nitric acid, nitrous acid, boric acid, phosphoric acid, phosphorous acid, and permanganic acid; the concentration of the acid solution is 0.1-20 mol / L; the mixing method is one or more of ball milling, sand milling, high-speed dispersion, ultrasonic dispersion, etc.; the stirring temperature is 20-100° C.; the stirring time is 30-300 min; and the drying method is vacuum drying.

3. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In step S2, the mass ratio of heteroatom elements to carbon elements in the modified carbon support material is 0.01-5%; the solvent is one or more of ethylene glycol, water, oleylamine, diphenyl ether, dibenzyl ether, o-dichlorobenzene, chloroform, and tetralin.

4. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In the step S3, the platinum source compound is one or more of chloroplatinic acid, platinum acetylacetonate, potassium chloroplatinate, and platinum chloride; the M metal source compound is one or more of cobalt acetate, cobalt hydroxide, cobalt chloride, cobalt nitrate, cobalt sulfate, basic cobalt carbonate, cobalt acetylacetonate III, cobalt acetylacetonate II, copper acetate, copper hydroxide, copper chloride, copper nitrate, copper sulfate, copper acetylacetonate, ferric acetate, ferric hydroxide, ferric chloride, ferric acetylacetonate, nickel acetylacetonate, nickel hydroxide, nickel chloride, zinc nitrate, zinc chloride, zinc acetylacetonate, and chromium chloride; the reducing agent is one or more of sodium hypophosphite, formaldehyde, sodium borohydride, tetradecanediol, dimethylaminoborane, and borane-tert-butylamine complex; the reaction temperature is 90-300° C., and the reaction time is 30-1200 min.

5. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In step S3, the molar ratio of the platinum element in the platinum source compound to the M element in the M metal source compound is (1:1)-(5:1); the mass ratio of the platinum element in the platinum source compound to the carbon carrier is (5:95)-(7:3).

6. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In the step S4, the reducing gas is hydrogen, acetylene, a hydrogen-inert gas mixture of a certain concentration, etc., the T1 temperature is 100-450° C., and the T1 temperature reaction time is 30-1200 min.

7. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In the step S4, the T2 temperature is 450-1000° C., and the T2 temperature reaction time is 30-1200 min.

8. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In step S5, the acid solution is one or more of perchloric acid, nitric acid, sulfuric acid, and acetic acid, the acid solution concentration is 0.01-0.5 mol / L, the reaction temperature is 40-100° C., the reaction time is 60-1200 min, the cleaning agent is water, and the drying method is vacuum drying.

9. The method for preparing an alloy catalyst for a fuel cell according to claim 1, characterized in that: In step S6, the reducing gas is hydrogen, acetylene and a certain concentration of hydrogen-inert gas mixture; the T3 temperature is 200-400°C, the reaction time is 30-1200min, and the mass fraction of heteroatom elements in the alloy catalyst is 0.005-2%.

10. The alloy catalyst for a fuel cell prepared by the method according to any one of claims 1 to 9, characterized in that: The alloy catalyst comprises a complex formed by platinum element and transition metal element, and the complex is supported on a carbon material; the transition metal is one or more of nickel, cobalt, iron, copper, chromium and zinc metal.

Citation Information

Patent Citations

  • Preparation method and application of ordered low-platinum alloy catalyst

    CN113113621A

  • Binary Pt-based ordered alloy fuel cell catalyst and preparation method thereof

    CN118231683A

  • Fuel cell carbon-supported Pt-based intermetallic compound catalyst and preparation method thereof

    CN118610501A

  • Sic ring packaging system

    KR1020250106872A